Eleven Years’ Experience of Sociodemographic and Clinicopathologic Characteristics of Endometrial Carcinoma Patients at a Tertiary Hospital - Binti H., Humairah; Dewi, Citra; Nurwany, Raissa (Majalah Patologi Indonesia, 2024)
Endometrial carcinoma is a malignant proliferation of the endometrium cells. This particular type of carcinoma is a world problem since it was ranked the second most common gynecology malignancy, and is the most common malignancy found in the uterus. This research is conducted to identify the sociodemographic and clinicopathologic characteristics of endometrial carcinoma patients at RSUP Dr. Mohammad Hoesin Palembang. This is an observational study with a cross-sectional design. Of all 37 samples collected, the majority are women of ages 20-50 (81,1%), married (83,8%), housewives (40,5%), and live within the city of Palembang (73%). Histopathologically, the most common subtypes found are endometrioid adenocarcinoma (62,2%), and of grade G3. The majority of the samples are within stage 1 cancer (27%), and with no metastases (83,8%). It can be concluded that, socio-demographically, the majority of endometrial carcinoma patients are aged 20-59 years, are married, work as housewives, and live in the city of Palembang, while the histopathological characteristics that are commonly found are the endometrioid adenocarcinoma subtype, grade G3 carcinoma, stage 1 carcinoma, and carcinoma without metastases.